"We Are Here": Race, Gender, and Spaces of "Common Ground" in the Works of John Edgar Wideman, bell hooks, and Jesmyn Ward. (27th September 2021) - Wendland-Liu, Joel
Abstract: Black-authored self-writing serves as a tool of cultural self-determination and anticipates the concept of "placemaking." Scholars regard "placemaking" as a process by which people of color struggle to transform space into place, to alter racially segregated spaces into sites of joy, freedom, and political mobilization. This essay evaluates these claims through an exploration of spatial themes in three memoirs: John Edgar Wideman–s Fatheralong (1994), bell hooks's Where We Stand (2000), and Jesmyn Ward's Men We Reaped (2013). The contemporary constructions of black place in these narratives destabilize ideological impressions of linear racial progress, individualism, dominant narratives of "colorblind" white supremacy, and neoliberal political economy. These texts record a process by which black people create a self-determined space of "common ground" despite white supremacist, capitalist dominance.